Admiralty Park : field monitoring and assessment of a rain garden system - Yeo, May Choo (2014)
Storm-water Best Management Practices (BMPs) was first developed in the early 1990s but such practices are relatively new in Singapore as it was only introduced by PUB in 2009. The performance of implemented BMPs in Singapore is hardly evaluated and implementers may be oblivious of whether these BMPs that they have designed are functioning as they are supposed to be. In this project, a recent constructed BMP system located at Admiralty Park was assessed on its performance in improving the water quality of the storm runoff. The system comprises several unit processes in the following order: sedimentation basin, sand filter bed, rain garden system and a wet pond. A 5-day consecutive grab sampling program was conducted to ascertain the background water quality where parameters such as iron concentration, DO, turbidity, pH, conductivity and temperature were measured. It was found that no iron was detected at the outlets of the sand filter, rain garden and pond. This finding suggests that these unit processes are capable of removing iron from the runoff. The same unit processes are also capable of removing suspended solids by reducing the turbidity level to less than 50 NTU with initial value of more than 200 NTU. In comparison with the turbidity levels at the pond outlet, the rain garden system was found to perform better at reducing turbidity to levels below the instrument detection level. Automatic discrete sampling was also conducted using auto-samplers and only two storm events were sampled due to the dry spell period. The removal efficiencies based on EMC computations for phosphorus components was much better than that of nitrogen components. Nutrient export was observed for all the nitrogen components and these components could be accumulated in the soil from previous storm events and was later released during the rainfall. However, these findings were not conclusive due to the small sample size and it is recommended to conduct additional sampling and analysis to obtain a more representative and statistically valid performance data. On the other hand, it was found that the concentrations of PO4 and NO3 in the outflow were within the allowable limits in the watercourse as regulated by NEA.